Modernisasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Pemahaman Internet sebagai Variabel Pemoderasi - Amiliasari, Ni Kadek Indah; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 31 No 7 (2021)DO - 10.24843/EJA.2021.v31.i07.p03, 2021)
E-system is a modernization of taxation system that uses information technology that makes it easier for taxpayers to report and pay their taxes. E-system consists of e-registration, e-SPT, e-filing, and e-billing This study aims to determine the effect of e-registration, e-SPT, e-filing, and e-billing on the compliance of individual taxpayers with internet understanding as moderating variable. Determination of the number of samples using incidental sampling technique. Linear regression test and Moderated Regression Analysis (MRA) are the data analysis technique used. The results showed that e-registration, e-SPT, e-filing, and e-billing has a positive effect on the compliance of individual taxpayers meanwhile e-registration, e-SPT, e-filing, and e-billing was not moderated by internet understanding on the compliance of individual taxpayers. Keywords: E-registration; E-SPT; E-filing; E-billing;  Taxpayer   Compliance; Internet Understanding.